The EIF SME Access to Finance Index - October 2022 Update - Wouter Torfs (European Investment Fund (EIF), 2022)
This working paper elaborates on the most recent update of the EIF SME Access to Finance (ESAF) Index, a composite indicator used to monitor the state of SME external financing markets in the EU. The current update, using data for 2021, constitutes the nineth iteration of this exercise, resulting in a 9-year long time series for each of the 27 EU countries. The latest data captures the impact of the COVID-pandemic and the subsequent policy response on SME access to finance. For an extensive overview of the current state of SME financing markets the reader is referred to the EIF's European Small Business Finance Outlook (Kraemer-Eis et al., 2022). The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by EIF's Research & Market Analysis and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330